Strain partitioning and mechanical stability of retained austenite - Ryu, Joo Hyun; Kim, Dong-Ik; Kim, Hyoung Seop; Bhadeshia, H. K. D. H.; Suh, Dong-Woo (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The mechanical stability of austenite in steels which rely on transformation-induced plasticity is usually attributed to its chemical composition, size and shape. We demonstrate here that another factor, the partitioning of strain between phases with different mechanical properties, can dramatically influence the stability. (C) 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: TRIP STEELS; DUAL-PHASE; BAINITE; MICROSTRUCTURE; FRACTION; SI